2018
DOI: 10.1074/jbc.ra118.004322
|View full text |Cite
|
Sign up to set email alerts
|

Elastin is heterogeneously cross-linked

Abstract: Elastin is an essential vertebrate protein responsible for the elasticity of force-bearing tissues such as those of the lungs, blood vessels, and skin. One of the key features required for the exceptional properties of this durable biopolymer is the extensive covalent cross-linking between domains of its monomer molecule tropoelastin. To date, elastin's exact molecular assembly and mechanical properties are poorly understood. Here, using bovine elastin, we investigated the different types of cross-links in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 64 publications
6
56
0
Order By: Relevance
“…Kagan et al reported the highest LOX activity for the synthetic polypeptide (AK) n . Our results, however, are in line with recently published data, especially with respect to specific Lys residues which are simultaneously involved in different molecular interconnections in bovine elastin [24]. However, the majority of the peptides derived from KA domains with Lys-Phe, Tyr-Lys or Lys-Tyr motifs was cross-linked via LNL.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Kagan et al reported the highest LOX activity for the synthetic polypeptide (AK) n . Our results, however, are in line with recently published data, especially with respect to specific Lys residues which are simultaneously involved in different molecular interconnections in bovine elastin [24]. However, the majority of the peptides derived from KA domains with Lys-Phe, Tyr-Lys or Lys-Tyr motifs was cross-linked via LNL.…”
Section: Discussionsupporting
confidence: 92%
“…While various previous studies focused on particular events of elastogenesis predominantly using immunohistochemical techniques [4,11,[29][30][31][32][33], elastin's molecular structure remains unknown. This workflow, which we applied also in this study, is based on the purification of elastin, its enzymatic hydrolysis and the subsequent analysis of the released peptides using an untargeted mass spectrometry-based sequencing approach [24]. We have recently introduced an approach to overcome these analytical challenges and to gain deeper insight into elastin's structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations